Tarot como sistemática para o desenvolvimento da criatividade - Rodrigues, Thiago Louis Gringon Souto (2024)
Starting from the premise that the components of different theories and models of creativity add complexity to understanding this construct, this study aimed to investigate the possibility of using Tarot (a deck composed of 78 illustrated cards used as an oracle for self-knowledge) as a metaphorical instrument to systematize these various conceptual components into a possible systemic model. This model would relate the iconography and symbolism of Tarot to studies on and for creativity. Through an experimental, exploratory, and qualitative research approach, which intertwined a literature review, a reflection on the author’s own journey as a tarot reader and creativity professor in higher education, and a methodological proposal with guidelines for complex thinking, metadesign, and the study of symbols, the study reflects on the connections between mysticism and creative development. It concludes that Tarot is a viable tool for fostering creativity. The research proposed as a final product a framework for the Tarot model of creativity, with the intention of later creating cards and books that explore this new iconography.